MODERN APPROACHES TO DIAGNOSTICS AND TREATMENT OF DENTAL TRAUMA - O.S. Ivanytska (Український стоматологічний альманах, 2020)
Relevance of the topic. Disruption of the anatomical integrity of the dentition, occurring as a result of dental trauma, not only impairs the patient’s appearance, but can also affect the functional properties of the entire maxillofacial area. Therefore, the choice of optimal methods for treatment of dental traumas remains an urgent problem of dentistry and requires further development.